Estimation of the mean AUC of the xenoestrogens daidzein, bisphenol A, and p-tert-octylphenol - Silvia Selinski; Gisela H. Degen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2003)
Potentially adverse human and environmental effects due to hormone mimicry of environmental estrogens are a matter of current concern. Environmental estrogens belong to the so-called endocrine active compounds (EAC), which alter signalling processes of the endocrine system leading to a broad range of effects during foetal and postnatal development, puberty, adulthood, and aging. A number of synthetic chemicals as well as several plant-derived compounds, so-called phytoestrogens, are known to have weak estrogenic activity. The present study is part of the risk assessment of the weak environmental estrogens daidzein, p-tert-octylphenol, and bisphenol A. The isoflavone daidzein is an important phytoestrogen with respect to dietary exposure (soy beans and soy products). p-tert-Octylphenol and bisphenol A are industrial chemicals. The toxicokinetics and the bioavailability of these three substances in female DA/Han rats after oral and single intravenous application were investigated by the use of population models accounting for the differences in the individual metabolism. Furthermore, populations of pregnant and non-pregnant rats are compared.
Keywords: 519; Bisphenol A; daidzein; p-tert-octylphenol; xenoestrogens; phytoestrogens; endocrine active compounds; bioavailability; AUC; population model; EM algorithm; Mann-Whitney-U-test